Molecular characterization and re-interpretation of HNF1A variants identified in Indian MODY subjects towards precision medicine - Kavitha, Babu; Ranganathan, Sampathkumar; Gopi, Sundaramoorthy; Vetrivel, Umashankar; Hemavathy, Nagarajan; Mohan, Viswanathan; Radha, Venkatesan (Frontiers in Endocrinology, 2023)
Background: HNF1A is an essential component of the transcription factor network that controls pancreatic β-cell differentiation, maintenance and glucose stimulated insulin secretion (GSIS). A continuum of protein malfunction is caused by variations in the HNF1A gene, from severe loss-of-function (LOF) variants that cause the highly penetrant Maturity Onset Diabetes of young (MODY) to milder LOF variants that are far less penetrant but impart a population-wide risk of type 2 diabetes that is up to five times higher. Before classifying and reporting the discovered variations as relevant in clinical diagnosis, a critical review is required. Functional investigations offer substantial support for classifying a variant as pathogenic, or otherwise as advised by the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) ACMG/AMP criteria for variant interpretation. Objective: To determine the molecular basis for the variations in HNF1A gene found in patients with monogenic diabetes in India. Methods: We performed functional protein analyses such as transactivation, protein expression, DNA binding, nuclear localization and Glucose stimulated insulin secretion (GSIS) assay, along with structural prediction analysis for 14 HNF1A variants found in 20 patients with monogenic diabetes. Results: Four out of 14 (28.6%) variants were interpreted as pathogenic; six (42.8%) as likely pathogenic; three (21.4%) as variants of uncertain significance and one variant (7.14%) as benign. Patients harboring the pathogenic/ likely pathogenic variants were able to successfully switch from insulin to sulfonylureas (SU) making these variants clinically actionable. Conclusion: Our findings are the first to show the need of using additive scores during molecular characterization for accurate pathogenicity evaluations of HNF1A variants in precision medicine.